2004
DOI: 10.1111/j.1365-2591.2004.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Shaping ability of ProTaper nickel‐titanium files in simulated resin root canals

Abstract: Under the conditions of this study, ProTaper instruments performed acceptable tapered preparations in all canal types. When using F2 and F3 in curved canals, care should be taken to avoid excessive removal at the inner curve, leading to danger zones. In addition, care should also be taken to avoid deformation of the F3 instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
0
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 20 publications
12
55
0
9
Order By: Relevance
“…However, the MPT or RPT had a few more zips and elbows than the PF. The reason may be over-uses of F series files in ProTaper � system which can remove tooth structure excessively when left in the canal too long with their active design 24) . It is therefore of utmost importance to follow the manufacturer' s instructions and not to leave the RPT prepare the root canal for longer than 1 second or not to use the MPT too much when reaching the desired working length.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…However, the MPT or RPT had a few more zips and elbows than the PF. The reason may be over-uses of F series files in ProTaper � system which can remove tooth structure excessively when left in the canal too long with their active design 24) . It is therefore of utmost importance to follow the manufacturer' s instructions and not to leave the RPT prepare the root canal for longer than 1 second or not to use the MPT too much when reaching the desired working length.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…The study using mathematic models have demonstrated that ProTaper instruments work longer in a super elastic phase than instruments with a Ufile design, allowing for high performance and less risk 20) . According to Calberson et al 21) , ProTaper instruments performed acceptable tapered preparations in all canal types. Iqbal et al 22) reported that ProTaper system is able to optimally enlarge root canal with minimal transportation and loss of working length in vitro study compared with ProFile system.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…The cross-section of Mtwo file is S-shape while that of ProTaper is triangular 18) . There were a few reports about Mtwo rotary 11,18,19) , however, several researches have been studied for the safety and the efficiency of crown-down technique using ProTaper system [20][21][22] . The study using mathematic models have demonstrated that ProTaper instruments work longer in a super elastic phase than instruments with a Ufile design, allowing for high performance and less risk 20) .…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Aletlerin pozitif rake açısı ve kesici olmayan bir uç şekli vardır. 55 Bu dizayn alet bıçakları-nın kanal duvarına temasını arttırmakta ve kök ucu yönünde konikleşen düz bir yüzey elde edilmesini sağlamaktadır.…”
Section: Protaperunclassified